Massive Ovarian Enlargement with Multiple Cysts Mimicking Ovarian Neoplasm and Primary Hypothyroidism (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Cystic enlargement of ovaries may develop due a large number of causesand may need surgical intervention. Moreover, some ovarian cysts arise due to endocrinedisorders & do not require surgery. We report an unusual case of massive enlargement ofovaries with multiple cysts in a girl with severe hypothyroidism. Morphologic features ofcysts on ultrasonography and clinical features of hypothyroidism with elevated TSH levelfacilitates diagnosis of multiple ovarian cysts and hypothyroidism.Case presentation: A 23-year-old unmarried woman presented with abdominal enlargement,pain and moderate anemia. Abdominal ultra sonogram revealed huge enlargement of theovaries with multiple large cysts. She was admitted in a hospital, treated with blood transfusionand laparotomy was decided. She was referred to us in a private clinic. On further evaluation, she had features of hypothyroidism with high TSH level and abdomino-pelvic ultrasoundrevealed enlarged ovaries with multiple large thin-walled cysts and mild ascitis. Conservativemanagement with thyroxin replacement therapy was given and after 3 weeks of thyroxine(T4) therapy, follow-up abdominal ultrasound showed significant reduction in ovarian size.After 4 months of thyroxine therapy, ovarian size normalized, cysts disappeared completelyand there was significant improvement of patient’s condition and she became euthyroid.Conclusion: This case report highlights the rare association between hypothyroidism andmulticystic ovarian enlargement. It is necessary to keep in mind the possibility ofhypothyroidism in the differential diagnosis of adult patients with ovarian enlargement andmultiple cyst formation in order to prevent unnecessary ovarian surgery.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 78-81